The hypolipidemic mechanism of chrysanthemum flavonoids and its main components, luteolin and luteoloside, based on the gene expression profile - Sun, Jihan; Wang, Zhaodan; Lin, Chen; Xia, Hui; Yang, Ligang; Wang, Shaokang; Sun, Guiju (Frontiers in Nutrition, 2022)
4 groups of Hyperlipidemia mice were involved in this study: the model control group (MC); Chrysanthemum flavonoids group (CF); luteolin group and luteoloside group. The whole gene expression profile was detected in liver tissues of each group. Differential genes significantly enriched in the biological process of GO items and KEGG were selected, and 4 differential genes related to lipid metabolism were selected for further real-time quantitative PCR verification. Compared with model control group (MC), 41 differential genes such as Sqle, Gck and Idi1 were screened in Chrysanthemum flavonoids intervention group (CF); 68 differential genes such as Acsl3, Cyp7a1 and Lpin1 were screened in Luteolin intervention group (CF); 51 differential genes such as Acaca, Cyp7a1 and Lpin1 were screened in Luteoloside group. The mechanism of chrysanthemum flavonoids to improve hyperlipidemia is very complex, mainly involving biological processes such as cholesterol and fatty acid metabolism and glycolysis, luteolin mainly involves the synthesis and transport of cholesterol, luteoloside mainly involves fatty acid metabolism.The functional pathways of Chrysanthemum flavonoids may not be completely the same as luteolin and luteoloside, and further study is needed on the mechanism of action of other components.